Critical creative pedagogies: a decolonial and indigenous approach using visual arts and creative writing - Rivera Santana, Carlos; Akhurst, Graham (The Australian Journal of Indigenous Education, 2019)
Abstract The following paper argues for a critical creative paedagogy as a means of meaningfully engaging with Indigenous and decolonial philosophies. We showcase our critical frameworks and pathways for teaching a decolonial and Indigenous university course where philosophy and arts meet to engage with complex colonial, racial and epistemological questions. We first frame our theoretical and philosophical stance within critical postcolonial, Indigenous and decolonial studies. We then describe an epistemological critique within western philosophical discourse that will gesture towards a decolonial pathway to arts and discuss our creative teaching approach grounded in decolonial and Indigenous theories. Lastly, we reach to a critical and decolonial space where ‘southern’ philosophies can be ‘heard’ in their fullest complexity. We contend that creative writing and visual arts grounded in critical decolonial and Indigenous theories provide a space in which a decolonised knowledge seems possible.